Strategi Majelis Tabligh Pimpinan Daerah Muhammadiyah Dalam Melaksanakan Program Safari Dakwah Di Kabupaten Sinjai - Nursyamsidar; St. Rahmatiah; Andi Abdul Hamzah (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This research delves into the Strategy of the Tabligh Assembly of the Muhammadiyah Regional Leadership in implementing the Da'wah Safari Program in Sinjai Regency. The formulation of the problem of this research is of significant importance: How is the strategy of the Muhammadiyah Regional Leadership Tabligh Assembly in implementing the da'wah safari program in Sinjai? This type of research is classified as qualitative with a da'wah and communication approach. Primary data sources came from the Regional Leadership of Muhammadiyah Kab. Sinjai and the Tabligh Assembly of the Regional Leadership of Muhammadiyah Kab. Sinjai. The data collection methods used, including observation, semi-structured interviews, and documentation, were chosen for their thoroughness. Data processing and analysis techniques are carried out through the stages of data collection, data reduction, data exposure, and data verification, with data validity guaranteed through triangulation of techniques, sources, and time. The results showed that the Tabligh Assembly of Muhammadiyah Sinjai Regional Leadership applied three primary strategies in the da'wah safari program: (1) Social transformation through Muhammadiyah charities in various regions, especially in the interior, to facilitate the spread of da'wah; (2) Cultural da'wah with an approach that accommodates local traditions, uses local languages and symbols, and involves traditional leaders in conveying Islamic values; and (3) Systematic and sustainable implementation of the safari da'wah program through regular regional scheduling, da'i cadre, and delivery of contextual da'wah material. The analysis of these strategies can be understood through the theoretical framework of social construction, symbolic interactionism, and structuration. The implications of this research are far-reaching, contributing significantly to the development of da'wah theories, particularly in the context of strategies for implementing the safari da'wah program. The study's results can be directly applied to refine existing strategies, guiding the selection of da'wah materials, delivery methods, and the application of cultural approaches. These refinements can have a tangible, positive impact on the understanding and practice of Islamic values in the lives of the people of Sinjai